INVESTIGATING THE EFFECT OF MODELING APPROACHES ON EARTHQUAKE BEHAVIOR OF HISTORICAL MASONRY MINARETS - BURSA GRAND MOSQUE CASE STUDY - Mutlu, Ozge; Sahin, Abdurrahman (YILDIZ TECHNICAL UNIV, 2016)
Earthquakes are considerable threats to historically and culturally significant buildings in Turkey, with its active tectonics and seismicity. Because of this, special care has to be taken for the protection and preservation of these structures against earthquakes for generations to come. Minarets are sensitive to strong winds along with earthquakes because of their slenderness. So, it is important to investigate behaviours of old and historically significant minarets under seismic forces. As an example of investigation and analysis of these structures subject to earthquake forces with the use of different structural modeling approaches, the eastern minaret of The Grand Mosque in Bursa, Turkey has been modeled in Sap2000 structural analysis software with the use of finite element method. Four different finite element models were produced for the analysis of this minaret and the modal analysis of all of them were carried out. With the use of acceleration data records taken during Kocaeli (1999) earthquake from the seismometer station closest to Bursa Grand Mosque, detailed seismic performance analyses were carried out in accordance with the four separate models. These separate analyses were used to investigate the differences of structural behaviour between different structural modeling approaches.
Keywords: Historical structures; minaret; eartquake analysis; modeling approaches; CONCRETE MINARETS; Engineering